Correlation between non-dominant foot placement variability with acceleration and agility performance in handball players - Ibrić Hasan; Rošker Jernej; Majcen-Rošker Živa (University Educons, Faculty of Sports and Tourism, Novi Sad, 2020)
The horizontal acceleration and agility are both an essential part of sports performance in handball. The foot placement variability has been shown to vary between differences in speed and direction of running. However, no studies have considered the connection between the foot placement variability, forward acceleration and agility performance. In the present study, a proposed repetitive single leg countermovement drift test was analyzed as a measure of the foot placement variability and correlated with forward sprinting and agility performance in handball players. Twenty-three male handball players performed a series of 10 consecutive single leg countermovement jumps, 10 m forward acceleration sprint, a handball adapted T-agility test and a single leg countermovement jump test. Correlations between the drift area, T-agility test duration, acceleration performance are measured as well as the time used to accelerate at a 5 m and 10 m distance and the height of the single leg countermovement jump. The drift area for the non-dominant leg had high and significant negative correlations with the first 5 m of forward acceleration sprinting and a positive correlation with the T-agility test to the non-dominant side. The countermovement jump height had no significant correlation to any other parameters. This data indicates that the foot placement variability of the jumps performed on the non-dominant leg could be an indicator of the ability to control stability during short forward acceleration sprints and a quick change of direction. On the contrary, these correlations disappeared when the direction change was performed under reaction time conditions.